EDFA based adaptive RZ-OOK transmission for FSO communication - Lv, Peng-Fei; Hong, Yan-Qing (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
This paper proposes an erbium-doped fiber amplifier (EDFA) based adaptive return-to-zero on-off keying (RZ-OOK) transmission for free-space optical (FSO) communication. EDFA has the characteristics of average power limitation. Therefore, the transmitted RZ-OOK duty cycle is varied for accomplishing pulse power variations relying on determined average signal-to-noise ratio of received signal. Thus, the atmospheric turbulent effects can be compensated by this type of adaptive RZ-OOK transmission. The channel models with different turbulence effects are established, and the proposed technique is validated in simulation. The simulation results illustrate that the communication quality of system is considerably enhanced by the proposed technique compared with fixed threshold decision and adaptive threshold decision.
Optica Applicata, Vol. 54, 2024, nr 2, s. 179-188
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; free-space optical communication; erbium-doped fiber amplifier; average signal-to-noise ratio; adaptive transmission